2020
DOI: 10.3390/antibiotics9070424
|View full text |Cite
|
Sign up to set email alerts
|

Non-Tuberculous Mycobacteria in Respiratory Specimens of Patients with Obstructive Lung Diseases—Colonization or Disease?

Abstract: Non-tuberculous mycobacteria (NTM) are increasingly a cause of human respiratory tract colonization and mycobacterial lung disease (NTM-LD), especially in patients with chronic lung diseases. The aim of the present study was to find the factors predictive of NTM-LD in patients with obstructive lung diseases and NTM respiratory isolates. A total of 839 isolates of NTM, obtained from 161 patients between 2010 and 2020 in a single pulmonary unit, have been retrospectively reviewed. Of these isolates, 73 concerned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This predisposition is difficult to comment on because bronchiectasis may be an early radiologic sign of NTMLD or one of the lung diseases predisposing to NTMLD. An analysis of the radiological appearance of NTMLD, performed by our group in COPD patients, revealed that 50% of patients with bronchiectasis were diagnosed with NTMLD, and the remaining had NTM colonization confirmed ( Szturmowicz et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This predisposition is difficult to comment on because bronchiectasis may be an early radiologic sign of NTMLD or one of the lung diseases predisposing to NTMLD. An analysis of the radiological appearance of NTMLD, performed by our group in COPD patients, revealed that 50% of patients with bronchiectasis were diagnosed with NTMLD, and the remaining had NTM colonization confirmed ( Szturmowicz et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…All of the patients with lung cavitation fulfilled the diagnostic criteria of NTMLD. Based on our experience, cavitary lesions on chest CT were the significant predictors of NTMLD not only in CF but also in COPD patients [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In all five described cases, M. a. was isolated from the samples from the respiratory tract. The presence of NTM in the respiratory tract does not always indicate pathology, as they can colonize the respiratory tract temporarily or permanently without inducing infection [ 22 , 23 ]. Establishing the etiological link of these bacteria to the disease can thus be complicated, and making decisions about the necessity of the targeted therapy can be very difficult [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%